DETERMINAN AKURASI PELAPORAN ASET DAERAH - Haryanto, Haryanto (JURNAL AKUNTANSI DAN AUDITING, 2014)
This study examines empirically internal factors (knowledge and ethical perception) and externalfactors (obedience pressure and task complexity) on accuration of asset reporting that wasprepared by pengguna barang/kuasa pengguna  barang. Sample  of the  study  used  sixty onesamples to the pengguna barang/kuasa pengguna barang who took duty on local governmentin Indonesia. Convinience sampling method is used as sampling method. This study usedquesionaire that were given directly to the pengguna barang/kuasa pengguna barang. Theanalyzis method was used in this study is double regression analysis. The study shows resultthat external factors (obedience pressure and task complexity) has no significant influence onaccuration of asset reporting that was prepared by pengguna barang/kuasa pengguna barang.However the internal factors (knowledge and ethical perception ) has significant influence onaccuration of  asset  reporting  that  was prepared  by  pengguna barang/kuasa pengguna barang.